2013
DOI: 10.1007/s40266-013-0072-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined Olmesartan, Amlodipine, and Hydrochlorothiazide Therapy in Randomized Patients with Hypertension: A Subgroup Analysis of the TRINITY Study by Age

Abstract: BackgroundHypertension is often inadequately controlled in older people.ObjectiveThis prespecified subgroup analysis assessed the efficacy and safety of an olmesartan medoxomil (OM) 40 mg/amlodipine besylate (AML) 10 mg/hydrochlorothiazide (HCTZ) 25 mg triple-combination treatment compared with the 3 components as dual-combination treatments in participants with hypertension who were <65 and ≥65 years of age. Within the ≥65 years of age subgroup, efficacy and safety were also summarized for participants ≥75 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The study showed that triple therapy was more effective in reducing BP than the component dual therapies, and a subsequent open‐label extension showed that reductions in BP were maintained over the long term (52 weeks) . Subgroup analyses from TRINITY have also shown that the improved efficacy of triple therapy was seen in major subgroups of patients, including those with diabetes, chronic kidney disease, or chronic CV disease, as well as those of black or Hispanic/Latino origin, those with advanced age, or those with obesity . The study by Volpe and colleagues showed that triple therapy is more effective than dual therapy at lowering BP across a range of doses.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that triple therapy was more effective in reducing BP than the component dual therapies, and a subsequent open‐label extension showed that reductions in BP were maintained over the long term (52 weeks) . Subgroup analyses from TRINITY have also shown that the improved efficacy of triple therapy was seen in major subgroups of patients, including those with diabetes, chronic kidney disease, or chronic CV disease, as well as those of black or Hispanic/Latino origin, those with advanced age, or those with obesity . The study by Volpe and colleagues showed that triple therapy is more effective than dual therapy at lowering BP across a range of doses.…”
Section: Discussionmentioning
confidence: 99%
“…The triple combination regimen with OM/AML/HCTZ, including high-dose OM 40 mg, was associated with significant BP reductions compared with any of the dual combination regimens at week 12 in the phase III TRINITY (triple therapy with olmesartan medoxomil, amlodipine besylate, and hydrochlorothiazide in adult patients with hypertension) study [ 10 , 11 ]. According to the subgroup analyses of the TRINITY trial, OM/AML/HCTZ was more effective for BP reductions than each of the dual regimens, irrespective of hypertension severity, age, or sex [ 10 , 12 ]. Other clinical studies reported that a triple combination of OM/AML/HCTZ provides effective BP reduction in patients whose BP is not controlled with a dual combination of OM/AML [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that a three-drug combination of ARB, CCB and HCTZ was more effective in achieving BP control when compared to a two-drug combination of the given classes (ARB/CCB, ARB/HCTZ, CCB/HCTZ). The regimen was well tolerated and effective in both elderly (≥ 65) and non-elderly (<65) groups [57].…”
Section: Combination Therapymentioning
confidence: 96%